2010
DOI: 10.1016/s0924-9338(10)70409-0
|View full text |Cite
|
Sign up to set email alerts
|

P01-203 - Presentation of a Specialized Outpatient Unit for Internet and PC Addiction -first Year of Operations, Results, Recommendations for the Future

Abstract: Methods: We present data from the first 40 adolescents who attended our service. Demographics and PC / Internet usage statistics are presented along with final diagnosis and treatment where it was deemed appropriate, both for Internet addiction disorder but also any co-morbid psychiatric disorder. We describe the diagnostic tests that are employed and their appropriateness for this goal and the therapeutic methods including psychotherapy (a sixteen session CBT protocol) and pharmacotherapy. Recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…When the effect of CBT on IAD was analyzed on the basis of geographical location, we observed that seven of these studies were carried out in China [23,25,45,76,77,78,79], two in Germany [70,33], two in Greece [62,63], three in USA [43,74], one in Korea [39], and one in Netherlands [65]. No work was retrieved from Australia, New Zealand, Africa or South America, possibly may be due to that different methods are being carried out in these regions for the treatment of IAD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When the effect of CBT on IAD was analyzed on the basis of geographical location, we observed that seven of these studies were carried out in China [23,25,45,76,77,78,79], two in Germany [70,33], two in Greece [62,63], three in USA [43,74], one in Korea [39], and one in Netherlands [65]. No work was retrieved from Australia, New Zealand, Africa or South America, possibly may be due to that different methods are being carried out in these regions for the treatment of IAD.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas one study was a survey research design that screened clients using Internet Addiction Test [74], three studies were case studies in which one focused on a single female college student [27], another was done on a teenage boy [43], and the third one on two male teenagers [63]. Similarly, one paper was of a descriptive study on IAD patients [62], one pilot trial [70] and one thematic analysis [65] which aims to identify themes within qualitative data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations